Starry messenger : cosmic perspectives on civilization [large type] - Tyson, Neil deGrasse (Thorndike Press large print nonfiction series., 2022)
"Scientific methods, tools, and discoveries have shaped modern civilization and created the landscape we've built for ourselves on which to live, work, and play. Tyson shows how an infusion of science and rational thinking renders worldviews deeper and more informed than ever before-and exposes unfounded perspectives and unjustified emotions. With crystalline prose and an abundance of evidence, Starry Messenger walks us through the scientific palette that sees and paints the world differently. From lessons on resolving global conflict to reminders of how precious it is to be alive, Tyson reveals, with warmth and eloquence, ten surprising, brilliant, and beautiful truths of human society, informed and enlightened by knowledge of our place in the universe" -- Back cover.